Hyperbaric Oxygen Treatment in Research and Clinical Practice Mechanisms of Action in Focus - Drenjančević, Ines (IntechOpen, 2018)
Hyperbaric oxygen treatment (HBO2) is a widely accepted adjuvant therapy in various health conditions that exhibit impaired tissue blood flow. At high pressures, the delivery of the dissolved oxygen in plasma is enhanced, which contributes to better tissue oxygenation, cellular metabolism and ultimately, healing. However, this is not the only beneficial outcome of HBO2 treatment since oxygen is a highly reactive molecule and can induce upregulation of many enzymatic systems in the cell at the cellular, genetic and molecular level. Particularly, vascular/endothelial function is affected by the HBO2. Our understanding of these mechanisms is still emerging. There have been many controversies related to the HBO2 protocols and indications. As well as exhibiting beneficiary effects on the tissue perfusion, it is known that HBO2 demonstrates high toxicity at higher pressures, due to increased oxidative stress and barotrauma. On the other hand, there is a lack of translation of the knowledge on the mechanisms of action of HBO2 obtained from the experimental research to the clinical practice. Thus, this book presents the reader with an overview of the current knowledge on the mechanisms of HBO2 effects in various experimental models and clinical treatment protocols, in an attempt to provide a better understanding of how and when HBO2 should be used as an effective therapy without unwanted side effects.